A new psychometrically validated questionnaire for assessing teacher agency in eight dimensions across pre-service and in-service teachers - Leijen, Äli; Pedaste, Margus; Baucal, Aleksandar (Frontiers in Education, 2024)
Teacher agency is an increasingly important area of research across different learning and professional development settings. In our study, we followed the ecological model of teacher agency and developed a questionnaire that allows us to differentiate eight dimensions of teachers' agency. Confirmatory factor analysis showed an acceptable fit of the eight-factor model in two different domains where teachers often make decisions: planning of teaching and learning activities and using information and communication technologies in teaching. Comparisons of configural, metric, and scalar models revealed good metric invariance across pre-service and in-service teachers in both agency domains. However, scalar invariance was not supported. Therefore, the new questionnaire seems suitable and sensitive for assessing teachers' agency in these groups separately, but comparisons of the groups should not be made.